International diversification of large business groups in Singapore. - Chua, Shin Ling. (2009)
The 1997 Asian Financial Crisis has greatly caused undesirable impact on the global economy, including Singapore. The lesson to be learnt from the crisis is the risk of concentrating business in one region. In order to minimise such risks faced by the corporate sectors in future, the Singapore government has strongly urged local companies to diversify internationally.